Relationship between BMI and prognosis of chronic heart failure outpatients in Vietnam: a single-center study - Nguyen, Hoai Thi Thu; Ha, Thuong Thi Thu; Tran, Hieu Ba; Nguyen, Dung Viet; Pham, Hung Manh; Tran, Phuong Minh; Pham, Tuan Minh; Allison, Thomas G.; Reid, Christopher M.; Kirkpatrick, James N. (Frontiers in Nutrition, 2023)
Background Insufficient data exists regarding the relationship between body mass index (BMI) and the prognosis of chronic heart failure (CHF) specifically within low- and middle-income Asian countries. The objective of this study was to evaluate the impact of BMI on adverse outcomes of ambulatory patients with CHF in Vietnam. Methods Between 2018 and 2020, we prospectively enrolled consecutive outpatients with clinically stable CHF in an observational cohort, single-center study. The participants were stratified according to Asian-specific BMI thresholds. The relationships between BMI and adverse outcomes (all-cause death and all-cause hospitalization) were analyzed by Kaplan–Meier survival curves and Cox proportional-hazards model. Results Among 320 participants (age 63.5 ± 13.3 years, 57.9% male), the median BMI was 21.4 kg/m2 (IQR 19.5–23.6), and 10.9% were underweight (BMI <18.50 kg/m2). Over a median follow-up time of 32 months, the cumulative incidence of all-cause mortality and hospitalization were 5.6% and 19.1%, respectively. After multivariable adjustment, underweight patients had a significantly higher risk of all-cause mortality than patients with normal BMI (adjusted hazard ratios = 3.03 [95% CI: 1.07–8.55]). Lower BMI remained significantly associated with a worse prognosis when analyzed as a continuous variable (adjusted hazard ratios = 1.27 [95% CI: 1.03–1.55] per 1 kg/m2 decrease for all-cause mortality). However, BMI was not found to be significantly associated with the risk of all-cause hospitalization (p > 0.05). Conclusion In ambulatory patients with CHF in Vietnam, lower BMI, especially underweight status (BMI < 18.5 kg/m2), was associated with a higher risk of all-cause mortality. These findings suggest that BMI should be considered for use in risk classification, and underweight patients should be managed by a team consisting of cardiologists, nutritionists, and geriatricians.